Application of Visual MODFLOW to the Analysis of Boundary Conditions for a Phreatic Porous Aquifer Using Limited Available Information: A Case Study - Almeida, Milena Stefany Lage; Gonçalves, José Augusto Costa (Anuário do Instituto de Geociências, 2021)
The increasing water demand, especially in developing regions, continuously puts pressure on groundwater resources both quantitatively and qualitatively. Hydrogeological modeling is a tool used in planning and management of groundwater resources. The factors that interfere in groundwater flow dynamics can be determined by developing a conceptual model and they can be validated via a numerical model. The objective of the manuscript is the hydrogeological groundwater flow modeling of the phreatic porous aquifer of the Ribeirão Candidópolis catchment in the Itabira municipality, State of Minas Gerais (Brazil). The software used in this study is GMS: MODFLOW, which enabled a steady state flow regime modeling by means of the Finite Difference Method (FDM) and the parameters calibration from a semi-transient approach. To assess the performance of the model, the Mean Error (ME), the Mean Absolute Error (MAE), and the Root Mean Square Error (RMSE) were calculated. The results proved to be compatible with the values observed in the field. After several adjustments of the boundary conditions, a Normalized Root Mean Square (NRMS) of 9.648% and a correlation coefficient of 0.993 were obtained. Despite the economic importance of the study area, studies made available on groundwater flow behavior are rare. The results obtained via modeling are in accordance with the data observed in the field and consequently our model can be used in the study of water level changes.